Cryptococcal meningitis disguised as a stroke: a case report - Muhamad Damanhuri, Fatimahtuz Zahrah; Zakariah, Siti Zulaikha; Abdul Ghani, Fatimatulzahra (UPM Press, 2022)
We present a case of cryptococcal meningitis initially misdiagnosed as stroke. Our patient is a young man on longterm corticosteroid due to gouty arthritis, who presented with acute onset of left-sided body weakness. Computed tomography of the brain revealed multifocal chronic lacunar infarcts with acute communicating hydrocephalus and cerebrospinal fluid culture isolated Cryptococcus neoformans. He was subsequently treated with amphotericin B and fluconazole but passed away due to multiorgan failure. This case report highlights the importance of considering chronic meningitis as a differential diagnosis when encountering stroke in young and immunocompromised patients.